Dark personality in dark times: How Dark Triad personality interacts with injustice and politics to influence detachment and discretionary behaviours. (6th July 2022) - Syed, Fauzia; Raja, Usman; Naseer, Saima
Abstract: Using two‐wave time‐lagged multi‐source data in two studies, we examine how Dark Triad personality (DTP) interacts with contextual variables to influence psychological detachment and discretionary behaviours. In Study 1 (N = 288), we examine the combined effects of DTP and perceived injustice on psychological detachment and organizational citizenship behaviours (OCBs). In Study 2 (N = 461), we examine the combined effects of DTP and perceived organizational politics (POP) on counterproductive work behaviours (CWB) and psychological detachment. We found that Dark Triad personality was positively related to psychological detachment and CWBs and negatively related to OCBs. The effects of the DTP on psychological detachment, OCBs, and CWBs were stronger when perceived injustice and POP was high. Résumé: En utilisant des données multi‐sources décalées dans le temps à deux vagues dans deux études, nous examinons comment la personnalité de la Triade noire (DTP) interagit avec des variables contextuelles pour influencer le détachement psychologique et les comportements discrétionnaires. Dans l'étude 1 (N = 288), nous examinons les effets combinés du DTP et de l'injustice perçue sur le détachement psychologique et les comportements de citoyenneté organisationnelle (OCB). Dans l'étude 2 (N = 461), nous examinons les effets combinés du DTP et de la politique organisationnelle perçue (POP) sur les comportements de travail contre‐productifs (CWB) et le détachement psychologique. Nous avons constaté que la personnalité de la triade noire était positivement liée au détachement psychologique et aux CWB et négativement liée aux OCB. Les effets du DTP sur le détachement psychologique, les OCB et les CWB étaient plus forts lorsque l'injustice perçue et le POP étaient élevés.